Empowered Women In The Digital Era: Leveraging Social Media For Change - Salam, Dikriyah; Sholahuddin Al Ayubi (Prodi Komunikasi Penyiaran Islam Sekolah Tinggi Agama Islam As-Sunnah, 2025)
Women have a very significant role in various areas of life, including social, cultural, and economic. However, gender injustice remains a significant global problem, where women often face discrimination in the areas of education, employment, and health. This research aims to explore how women use social media as a means to fight for gender equality and reduce the influence of patriarchy. By applying a qualitative approach and thematic analysis of the hadith, this study identifies women's understanding and experiences in the digital world, and connects them to the teachings of Islam that support their positions and roles. The findings of the study suggest that social media serves as a platform to spread kindness, strengthen social relationships, and prevent abuse, while providing opportunities for women to emerge as leaders in modern society. This study emphasizes the importance of women's empowerment and the achievement of gender equality as key factors in realizing sustainable and inclusive development.